Love Thy Neighbour? Evidence from Ethnic Discrimination in Information Sharing within Villages - Mattia Romani (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2004)
There is increasing evidence to suggest that a fundamental source of information for farmers on how to access and use new agricultural technologies comes from interacting with neighbours. Economic research on adoption of innovations in a rural context has only partially addressed the issue of how the social structure of a village can affect adoption and the final impact on productivity of farmers. This paper investigates the role of proximity interpreted not only in geographical terms but also along the line of ethnic similarities among neighbours (what we define as ?social proximity?). We use a panel dataset collected in C.te d?Ivoire to define the probability of accessing the knowledge network. The main results indicate that farmers from ethnic minorities are less likely to access, and benefit less from, extension services. But they seem to try to re-equalize their condition by putting more effort than dominant ethnic group neighbours in sharing information among themselves.
Keywords: 330; economic development; technological change; growth